ANALISIS KEMAMPUAN SISWA KELAS V DALAM PENGGUNAAN HURUF KAPITAL DI SD NEGERI 161 PEKANBARU - Rina Afriyeni; Otang Kurniaman; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is still often mistakes in the use of capital letters in class V SD Negeri 161 Pekanbaru. In fact, in class III semester I have been taught about the rules of the use of capital letters. Such errors often occur in student writing. Even the students seem to be accustomed to writing without regard to the use of capital letters The purpose of this study is to know and describe the ability of grade V students in the use of capital letters in SD Negeri 161 Pekanbaru. The type of research used in this study is descriptive quantitative. Descriptive research is a study that attempts to describe a phenomenon, events, events that occur in the present moment. This research was conducted in the odd semester of academic year 2016/2017 on 13-15 December 2017. Sampling in this study using sampling technique in the form of census (Sampling saturated). The sample in this research is the entire class V in SD Negeri 161 Pekanbaru which amounted to 85 students. The data collection instrument used is a matter of multiple choice test. The results showed that the ability of students in the use of capital letters in SD Negeri 161 Pekanbaru as a whole indicators fall into the category of less able When viewed per indicator, there are 7 indicators that fall into the category of less able and as many as 5 indicators that fall into the category quite capable.Keywords : The Use of Capital Letters